Roundabout users subjective safety - case study from Upper Silesian and Masovian Voivodeships (Poland) - Macioszek, Elzbieta; Kurek, Agata (Transactions on Transport Sciences, 2020)
The main objective of the work was inventory intersections like roundabouts in all cities with poviat rights located in two voivodeships of Poland: Upper Silesian and Masovian, and then performing users surveys of registered roundabouts. Survey research had two main objectives. The first one was to learn how vehicle drivers, pedestrians and cyclists perceived roundabouts as safe or unsafe road solutions. The second one was to learn about the behaviour of three users groups: vehicle drivers, pedestrians and cyclists on this type of road infrastructure in terms of traffic safety.
Keywords: Roundabouts; road users behaviours; questionnaires; subjective safety; preference studies; road traffic safety; road traffic engineering; road transport.